2018
DOI: 10.3390/w10070831
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Characteristics of Several Bioretention-Modified Fillers for Phosphorus

Abstract: To optimize the bioretention mixed fillers with better removal of phosphorus, this paper studies the adsorption characteristics of single filler and modified mixed filler through static adsorption experiments, and adopts the dynamical mini-column experiments to examine the adsorption capacities of the soil and modified mixed fillers. Results show that, in the static adsorption experiments, both water treatment residual (WTR) and fly ash exhibit good adsorption capacity when used as a single filler and modifier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Phosphorus is removed by plants and microbial uptake or absorbed by the filter media (Marvin et al, 2020). Many studies focused on the efficacy and the mechanism involved in nitrogen (Jiang et al, 2017;Tian et al, 2019;Wu et al, 2017) and phosphorus (Chang et al, 2019;Zhang et al, 2018a) removal, but few studies have examined the long-term performance in SBS (Table 2). Previous research suggested that SBS could reduce nutrients after a long-term operation.…”
Section: Nutrientsmentioning
confidence: 99%
“…Phosphorus is removed by plants and microbial uptake or absorbed by the filter media (Marvin et al, 2020). Many studies focused on the efficacy and the mechanism involved in nitrogen (Jiang et al, 2017;Tian et al, 2019;Wu et al, 2017) and phosphorus (Chang et al, 2019;Zhang et al, 2018a) removal, but few studies have examined the long-term performance in SBS (Table 2). Previous research suggested that SBS could reduce nutrients after a long-term operation.…”
Section: Nutrientsmentioning
confidence: 99%
“…Then, the modified media were prepared by mixing modifiers including water treatment residue (WTR), green zeolite (Gz), medicinal stone (Ms), vermiculite, turfy soil (Ts), coconut bran, and fly ash and BSM with different proportions [22]. Selection and proportion of modifiers are determined by previous adsorption experiments [23]. In the static adsorption experiments, the modifiers with good adsorption capacity were selected.…”
Section: Media Preparationmentioning
confidence: 99%
“…Marvin et al [5] have recently presented a systematic literature review of phosphorous sorption in bioretention media. They note that a number of other researchers have more recently conducted laboratory or mesocosm scale tests of phosphorus retention with fly ash amended filter media [6][7][8][9][10][11][12]. Those tests showed that fly ash is generally superior to other additives for phosphorus reduction.…”
Section: Introductionmentioning
confidence: 99%